Design of robust load-frequency stabilizers of SMES in coordination with SSSC - Ngamroo, I.; Dechanupaprittha, S.; Hongesombut, K.; Mitani, Y.; Kunakorn, A. (My University, 2005)
This paper presents a design of robust load-frequency stabilizers of a superconducting magnetic energy storage (SMES) in coordination with a static synchronous series compensator (SSSC). As large load disturbances with changing frequency in the vicinity of the inter-area oscillations mode occur in an interconnected power system, a system frequency may be heavily perturbed and oscillatory. To stabilize frequency oscillations, a coordinated SMES with SSSC can be applied. On the other hand, variations of system parameters, several load changes etc., cause system uncertainties. To take such uncertainties into account, the multiplicative uncertainty is included in a system modeling. The structure of frequency stabilizer equipped with SMES and SSSC is a second-order lead/lag compensator. Control parameters of frequency stabilizers are automatically tuned by a tabu search. Simulation studies in a two-area interconnected power system confirm the effect of coordinated SMES with SSSC.
Keywords: Load-frequency stabilization; Robust stability; SMES; SSSC; System uncertainties